Life satisfaction and support for tourism development - Woo, E.; Kim, H.; Uysal, Muzaffer (Elsevier Ltd, 2015)
The purpose of this study is to better understand local residents' support for tourism development by exploring residents' perceived value of tourism development, life domain satisfaction (material/non-material), and overall quality of life in their community. The study provides the theoretical and empirical evidence of the relationships among those constructs. Using a sample of residents from five different tourism destinations, the results of a structural equation modeling approach indicated that residents' perceived value of tourism development positively affects non-material and material life domain satisfaction; thereby, it contributes to overall quality of life. Finally, overall quality of life is an effective predictor of support for further tourism development.